2014
DOI: 10.1063/1.4868964
|View full text |Cite
|
Sign up to set email alerts
|

The category of Yetter-Drinfel'd Hom-modules and the quantum Hom-Yang-Baxter equation

Abstract: Representations of the quantum doubles of finite group algebras and spectral parameter dependent solutions of the Yang-Baxter equationIn this paper, we introduce the category of Yetter-Drinfel'd Hom-modules which is a braided monoidal category and show that the category of Yetter-Drinfel'd Hom-modules is a full monoidal subcategory of the left center of left Hommodule category. Also we study the equivalent relationship between the category of Yetter-Drinfel'd Hom-modules and the category of Hom-modules over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…15),(4.4) = d ⊗ h, finishing the proof.Assume now that we are in the hypotheses of Proposition 4.3 and consider the Hom-L-Rsmash product D ♮ H = D Q ⊗ R H. Since the map Q is bijective, we can apply Proposition 2.4 and we obtain that the map P : H ⊗ D → D ⊗ H, P = Q −1 • R is a Hom-twisting map and we have an isomorphism of Hom-associative algebras Q : D ⊗ P H ≃ D ♮ H.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…15),(4.4) = d ⊗ h, finishing the proof.Assume now that we are in the hypotheses of Proposition 4.3 and consider the Hom-L-Rsmash product D ♮ H = D Q ⊗ R H. Since the map Q is bijective, we can apply Proposition 2.4 and we obtain that the map P : H ⊗ D → D ⊗ H, P = Q −1 • R is a Hom-twisting map and we have an isomorphism of Hom-associative algebras Q : D ⊗ P H ≃ D ♮ H.…”
mentioning
confidence: 64%
“…Yetter-Drinfeld modules over Hom-bialgebras were studied in [38] and we will introduce the Drinfeld double in this paper. Since Hom-bialgebras and monoidal Hom-bialgebras are different concepts, it turns out that our definitions, formulae and results are also different from the ones in [15,31].One of the main tools to construct examples of Hom-type algebras is the so-called "twisting principle" which was introduced by D. Yau for Hom-associative algebras and since then extended to various Hom-type algebras. It allows to construct a Hom-type algebra starting from a classicaltype algebra and an algebra homomorphism.The twisted tensor product A⊗ R B of two associative algebras A and B is a certain associative algebra structure on the vector space A ⊗ B, defined in terms of a so-called twisting map R : B ⊗ A → A ⊗ B, having the property that it coincides with the usual tensor product algebra A ⊗ B if R is the usual flip map.…”
mentioning
confidence: 99%
“…A (co)monoid in the Hom-category is a Hom-(co)algebra, and a bimonoid in the Hom-category is a monoidal Hom-bialgebra. Further research on monoidal Hom-bialgebras can be found in [22], [23], and [14].…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Shen [15] also studied Yetter-Drinfeld modules over monoidal Hom-bialgebras, they called them Hom-Yetter-Drinfeld modules, and showed that the category of Hom-Yetter-Drinfeld modules is a braided monoidal categories. Chen and Zhang [8] introduced the category of Hom-Yetter-Drinfeld modules, which is differs from that of [15], and indicated that it is a full monoidal subcategory of the left center of left Hom-module category. In [10], we defined the category of Doi Hom-Hopf modules and proved that the category of Hom-Yetter-Drinfeld modules is a subcategory of our category of Doi Hom-Hopf modules.…”
Section: Introductionmentioning
confidence: 99%